Physical and Psychological Impact on Children Undergoing Chemotherapy - Maharani, Tiara; Zukhra, Ririn Muthia; Putri, Syeptri Agiani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cancer is a non-communicable disease in which cells or tissues grow uncontrollably and malignantly and require long-term treatment. Chemotherapy is the primary treatment used to treat cancer by giving a type of drug that is tailored to the type of cancer suffered by the child. The mechanism of action of chemotherapy drugs is very strong to kill cancer cells but this also affects other normal cells. This shows that chemotherapy has side effects in its treatment. The side effects of chemotherapy are physical and psychological impacts. Objective: this study aims to determine the physical and psychological impact on children who undergo chemotherapy. This research was conducted at Arifin Achmad Regional Hospital. Methods: This research design uses descriptive quantitative with cross sectional approach. The sample of this study was 66 respondents. Sampling used a purposive sampling technique with inclusion criteria namely children who received chemotherapy treatment and were aged 5 to 7 years. The analysis used was univariate analysis. Results: The results of this study show that the physical impacts that often arise are hair loss (71.4%), dry mouth (40.5%), lack of energy (38.1%), changes in skin color (38.1%), nausea (38.1%), weight loss (35.7%) and others. Frequent psychological effects were irritability (69.0%), sleep disturbance (42.9%), worry (31.0%) and others. sadness (28.6%) and others. Conclusion: From the results of the study, it can be seen that the most frequent impacts on children undergoing chemotherapy are hair loss and irritability.